The pattern of a relational understanding of fifth-grade students on integer operations - Utomo, Dwi Priyo (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
Relational understanding constitutes studentsâ€™ awareness of appropriate procedures to solve problems along with logical reasoning. Â Itis pivotal to help students solve problems in mathematics. It is necessary that the teaching of mathematics be directed to achieve relational understanding. Accordingly, students are capable of solving complicated problems in mathematics. This current research aims at analyzing and describing relational understanding and the patterns of answering questions of the fifth graders on integer operation. This study used a qualitative approach with a case study as the research design. Further, three students belonging to the fifth grade of Elementary School in Malang City, Indonesia, were set up as the research subjects. A test was administered to measure the subjects' relational understanding. All collected data were analyzed using an interactive technique. The result has indicated that the highly-proficient student was able to show excellent relational understanding. Besides, it was shown that the fairly-proficient student could show good relational understanding. The lowly-proficient student was shown to be able to achieve only half of the holistic criteria set for relational understanding. The patterns of answering the questions demonstrated by all students in all levels included jotting down the models, completing the models, and answering the questions. The highly-proficient student understood the information and wrote it down. Whilst the fairly-proficient student understood the information without translating it into the written form. At last, the lowly-proficient student did not pronounce any signals of understanding of the information